2000
DOI: 10.1034/j.1399-0020.2000.290519-4.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic significance of laminin-5 gamma2 chain expression in squamous cell carcinoma of the tongue - immunohistochemical analysis of 67 lesions

Abstract: The laminin‐5 γ2 chain plays an important role in cell migration during tumour inva‐sion and tissue remodelling. Laminin‐5 γ2 chain expression in squamous cell carcino‐mas of the tongue in 67 patients with Stage II, III or IVA,B (excluding the cases with distant metastasis) was examined immuno‐histochemically to determine its associa‐tions with the clinicopathological features of each tumour. The predominant staining patterns were categorised as follows: A, few or no tumour cells were positive; B, part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
77
3
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 0 publications
10
77
3
1
Order By: Relevance
“…8 Besides, LAMC2 monomer expression has been frequently found in the invasive front of epithelial tumors such as ADCs of the stomach, colon, pancreas, and lung, SCCs of the esophagus, head and neck, skin and lung, and transitional cell carcinoma of the bladder. 5,[9][10][11][12][13][14] Epithelialmesenchymal transition (EMT) has a critical role in the early stages of dissemination of malignant epithelial tumors leading to metastatic spread. 15 There is growing evidence that LAMC2 expression increases in the carcinoma cells undergoing EMT, [16][17][18] and that level of LAMC2 expression is regulated directly by the EMT master regulator ZEB1 and activated β-catenin in invasive colorectal carcinoma cells.…”
mentioning
confidence: 99%
“…8 Besides, LAMC2 monomer expression has been frequently found in the invasive front of epithelial tumors such as ADCs of the stomach, colon, pancreas, and lung, SCCs of the esophagus, head and neck, skin and lung, and transitional cell carcinoma of the bladder. 5,[9][10][11][12][13][14] Epithelialmesenchymal transition (EMT) has a critical role in the early stages of dissemination of malignant epithelial tumors leading to metastatic spread. 15 There is growing evidence that LAMC2 expression increases in the carcinoma cells undergoing EMT, [16][17][18] and that level of LAMC2 expression is regulated directly by the EMT master regulator ZEB1 and activated β-catenin in invasive colorectal carcinoma cells.…”
mentioning
confidence: 99%
“…Laminin g 2 is not detectable immunohistochemically in the basal cells of normal epithelium but frequently is expressed abnormally by cells in the basal layer of invading fronts of many carcinomas [21][22][23] and also by some basal cells in many oral and interfollicular epidermal dysplasias. 24,25,29 Our recent study of oral dysplasias found that laminin g 2 overexpression occurs solely within regions that immunostain for p-S6(ser235/236) in the basal layer.…”
Section: The Relation Of Laminin C 2 Overexpression To Basal P-s6 Immmentioning
confidence: 99%
“…[21][22][23] More recently it was found that laminin g 2 overexpression begins at the preinvasive dysplastic stage of neoplastic progression in the oral epithelium and interfollicular epidermis. 24,25 Squamous cell carcinomas of the interfollicular epidermis, oral cavity, oropharynx, and lung very frequently have gene mutations and amplifications that hyperactivate their EGFR/ERK signaling pathway.…”
mentioning
confidence: 99%
“…Mouse monoclonal antibody 1-97, specific to the laminin-5-␥-2 chain, was established in our laboratory as described by Ono et al (15). We used this antibody for our immunohistochemical study.…”
Section: Laminin-5-␥-2-chain Immunohistochemistrymentioning
confidence: 99%
“…Between each step, the slides were washed three times with phosphate buffered saline. The positive control was a section of formalin-fixed, paraffinembedded tissue of squamous cell carcinoma of the tongue, described elsewhere (15).…”
Section: Laminin-5-␥-2-chain Immunohistochemistrymentioning
confidence: 99%